Internet Applications for Screening and Brief Interventions for Alcohol in Primary Care Settings – Implementation and Sustainability - Wallace, Paul; Bendtsen, Preben (Frontiers in Psychiatry, 2014)
Screening and brief interventions head the list of effective evidence-based interventions for the prevention and treatment of alcohol use disorders in healthcare settings. However, healthcare professionals have been reluctant to engage with this kind of activity both because of the sensitive nature of the subject and because delivery is potentially time-consuming. Digital technologies for behavioural change are becoming increasingly widespread and their low delivery costs make them highly attractive. Internet and mobile technologies have been shown to be effective for the treatment of depression, anxiety and smoking cessation in healthcare settings, and have the potential to add substantial value to the delivery of brief intervention for alcohol. Online alcohol questionnaires have been shown to elicit reliable responses on alcohol consumption and compared with conventional prevention techniques, digital alcohol interventions delivered in various settings have been found to be as effective in preventing alcohol-related harms. The last decade has seen the emergence of a range of approaches to the implementation in health care settings of referral to Internet based applications for screening and brief interventions (eSBI) for alcohol. Research in this area is in its infancy, but there is a small body of evidence providing early indications about implementation and sustainability, and a number of studies are currently underway. This paper examines some of the evidence emerging from these and other studies and assesses the implications for the future of eSBI delivery in primary care settings.